Nanobodies targeting immune checkpoint molecules for tumor immunotherapy and immunoimaging (Review) - Yu, Sheng (Int J Mol Med, 2021)
The immune checkpoint blockade is an effective strategy to enhance the anti-tumor T cell effector activity, thus becoming one of the most promising immunotherapeutic strategies in the history of cancer treatment. Several immune checkpoint inhibitor have been approved by the FDA, such as anti-CTLA-4, anti-PD-1, anti-PD-L1 monoclonal antibodies. Most tumor patients benefitted from these antibodies, but some of the patients did not respond to them. To increase the effectiveness of immunotherapy, including immune checkpoint blockade therapies, miniaturization of antibodies has been introduced. A single-domain antibody, also known as nanobody, is an attractive reagent for immunotherapy and immunoimaging thanks to its unique structural characteristic consisting of a variable region of a single heavy chain antibody. This structure confers to the nanobody a light molecular weight, making it smaller than conventional antibodies, although remaining able to bind to a specific antigen. Therefore, this review summarizes the production of nanobodies targeting immune checkpoint molecules and the application of nanobodies targeting immune checkpoint molecules in immunotherapy and immunoimaging.